From Opium to Shabu: A Flashback to the History of Narcotics in Indonesia - Riyadi, Riyadi (The Indonesian Journal of Social Studies, 2022)
From the case of the arrest of the perpetrators of the smuggling of one tonne of methamphetamine from China on the Wanderlust ship in Banten, and previously on March 1, 2017 in Medan, the perpetrators of narcotics smuggling from China were also caught with the type of methamphetamine weighing 12.72 grams, ecstasy as many as 3,702 pills, happy five as much as 454 points can provide clues about the existence of an organized motive from China to control Indonesia through narcotics or at least become a major player in the narcotics market in Indonesia. If traced through history, the opium culture in Indonesia is not a native Indonesian culture but was born as a result of the influence of Chinese migrants. This study aims to prove the pattern carried out by Chinese migrants in Indonesia related to narcotics from the colonial period to the present as well as the development of the culture of using opium from each period as well as regulation through the law against narcotics abuse.